2016
DOI: 10.3762/bjnano.7.23
|View full text |Cite
|
Sign up to set email alerts
|

Surface coating affects behavior of metallic nanoparticles in a biological environment

Abstract: SummarySilver (AgNPs) and maghemite, i.e., superparamagnetic iron oxide nanoparticles (SPIONs) are promising candidates for new medical applications, which implies the need for strict information regarding their physicochemical characteristics and behavior in a biological environment. The currently developed AgNPs and SPIONs encompass a myriad of sizes and surface coatings, which affect NPs properties and may improve their biocompatibility. This study is aimed to evaluate the effects of surface coating on coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 74 publications
6
54
0
1
Order By: Relevance
“…Our results suggested that the internalization of both types of the nanoparticles occurred via macropinocytosis as confirmed by TEM. Recently, PLL-γ-Fe 2 O 3 agglomeration properties were studied in biological cell culture media with or without common serum protein, which showed the increase of size and negative ζ-potential in comparison to ultrapure water [26]. Similarly to the other studied nanoparticles, the observed changes were less pronounced in coated than in uncoated particles, and in the presence of serum protein than in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the internalization of both types of the nanoparticles occurred via macropinocytosis as confirmed by TEM. Recently, PLL-γ-Fe 2 O 3 agglomeration properties were studied in biological cell culture media with or without common serum protein, which showed the increase of size and negative ζ-potential in comparison to ultrapure water [26]. Similarly to the other studied nanoparticles, the observed changes were less pronounced in coated than in uncoated particles, and in the presence of serum protein than in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the exceptional properties, these NPs may be used for targeted drug and contrast delivery, photothermal therapy, optical sensing, biochromatography, bioanalytical electrochemistry, biocidal agents and coatings, or a variety of bioassays (1)(2)(3)5).…”
mentioning
confidence: 99%
“…Recent advances in nanomedicine have resulted in the development of biodegradable nanodrug delivery systems, nanocrystals for magnetic resonance imaging (MRI), and luminescent NPs for multiplexed molecular diagnostics (1,3,5,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations